Dampak Kesehatan Pasca Aborsi - Arif Agung Winarto (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
Abortion or the scientific language is Abortus Provocatus, is the method most often used to end an unwanted pregnancy, even though it is the most dangerous method. Abortus Provocatus is divided into two types, namely Abortus Provocatus Therapeuticus and Abortus Provocatus Criminalis. Abortus Provocatus Therapeuticus is an abortion provocatus carried out on the basis of medical considerations and carried out by personnel who have received special education and can act professionally. Meanwhile, Abortus Provocatus Criminalis is an abortion provocatus that is done secretly and usually by personnel who are not specially educated, including pregnant women who want to carry out the abortion provocatus. Abortus Provocatus Criminalis is one of the causes of death of women during their fertile period in developing countries.